Comparative modeling, structure and active site prediction of Sclerotinia disease-resistant gene BnaMPK3 in Oilseed rape (Brassica napus) - Zeshan Haider; Muzdalfa Zulfiqar; Iqrar Ahmad Rana; Rao Sohail Ahmad Khan; Muhammad Numan Akram; Adnan Khan Niazi (Open Journal of Bioinformatics and Biostatistics - Peertechz Publications, 2020)
The prerequirement of genetic engineering is to have knowledge about structure and function of transgene and its encoded protein. This could be possible through in Insilco analysis of protein through protein comparative modeling which is a recent and important technique, used for the prediction of the protein three-dimensional (3D) structure. Fungal pathogen Sclerotinia sclerotiorum cause yield reduction about 15-20% in Brassica napus. Brassica napus mitogen-activated protein kinase 3 gene (BnaMPK3) codes for a BnaMPK3 protein that confers resistance against Sclerotinia sclerotiorum in oilseed rape. Computationnal analysis of primary structure, functional domains and S-Nitrosylation studies revealed that BnaMPK3 had five domains (protein kinases, kinases like superfamily, MAP kinase CS, Ser/Thr kinase AS, and protein ATP binding) and six S-Nitrosylation active sites at positions 53,141,176,181,227 and 336 respectively. The comparative modeling of the BnaMPK3 protein through Swiss-Model predicted 76.88% identity with template 6dtl.2A. 3-D structure of BnaMPK3 protein was validated through Errat score, which was 93.023%, indicated that it is stable protein. A total of 20 active sites were predicted by using ADDS (Automated active sites detection; docking; and scoring) software and active site with the highest overall quality score (ARG-72, ALA-77, ASP-115, VAL-151, ASP-155, LEU-156, ARG-173, PHE-174, GLY-175, ARG-178, PRO-179, THR-180, ARG-193, LEU-201, SER-205, and TYR-207) was used in further studies. The information achieved will be helpful to manipulate for sustainable resistance against sclerotinia disease in B. napus.